ANALISIS PERBANDINGAN MATERI PEMBELAJARAN BAHASA ARAB DI KELAS X MAN 2 KOTA BOGOR DAN MATTAYOM 4 DARULAMAN MULNITI SCHOOL - Dinda Lailatun Nazilah; Syarifah Gustiawati; Yono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of Arabic as the language of the Qur'an and the primary source of Islamic literature, alongside the differing educational contexts between Muslim-majority and Muslim-minority countries, which influence the development of Arabic learning materials. This study aims to identify the content of Arabic learning materials in Grade X at MAN 2 Kota Bogor, Indonesia; identify the content of Arabic learning materials in Mattayom 4 at Darulaman Mulniti School, Thailand; and analyze the similarities and differences between the Arabic learning materials in both schools. This study employed a qualitative approach with a comparative study method and a library research design. Data were collected through document analysis of textbooks and curricula, as well as interviews with Arabic teachers from each school. The results indicate that the Arabic learning materials at MAN 2 Kota Bogor are developed based on the Kurikulum Merdeka (Independent Curriculum), focusing on mastering the four language skills: istima' (listening), kalam (speaking), qira'ah (reading), and kitabah (writing), through themes closely related to students' daily lives. Meanwhile, the learning materials at Mattayom 4 Darulaman Mulniti School are developed based on the Thailand Arabic Language Learning Standards, emphasizing communication through themes related to travel, the professional world, and the linguistic environment. The similarities lie in their objectives of developing communication skills, teaching reading and writing, grammar, vocabulary, and conducting evaluations. The differences are found in the foundational framework of material development, the learning themes, and the specific focus of Arabic competence development.